-7(-3v+2)-5v=2(v-1)-4

Simple and best practice solution for -7(-3v+2)-5v=2(v-1)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(-3v+2)-5v=2(v-1)-4 equation:



-7(-3v+2)-5v=2(v-1)-4
We move all terms to the left:
-7(-3v+2)-5v-(2(v-1)-4)=0
We add all the numbers together, and all the variables
-5v-7(-3v+2)-(2(v-1)-4)=0
We multiply parentheses
-5v+21v-(2(v-1)-4)-14=0
We calculate terms in parentheses: -(2(v-1)-4), so:
2(v-1)-4
We multiply parentheses
2v-2-4
We add all the numbers together, and all the variables
2v-6
Back to the equation:
-(2v-6)
We add all the numbers together, and all the variables
16v-(2v-6)-14=0
We get rid of parentheses
16v-2v+6-14=0
We add all the numbers together, and all the variables
14v-8=0
We move all terms containing v to the left, all other terms to the right
14v=8
v=8/14
v=4/7

See similar equations:

| -0.54x+0.34x=6.2 | | Y=24x+42 | | 32=6v=(2v+8) | | 1/3x+8=184/6 | | x^2-x-2186.88=0 | | 2x-6=-3(x-8) | | (5y+4)(y-3)=0 | | -2x|x+4|-4=-12 | | 15-0.22x=9.06 | | (40+x)×(.20)=66 | | 15/25=66/x | | 2{x+4}=4x+3-2x+5 | | 15.99+0.96x=167.67 | | 3x=2x/3x | | 2+0.12x=9.56 | | A=7(x-4)+(6x-5)(-3x+4) | | 2.5n+10=2.5n+0.5n+10 | | 4.6=3x-5.4 | | 2e+-7=-11 | | F(x)=-5+20 | | 2.5(8x+2)=4(5x-1) | | 0.10=x/0.02 | | 3x+3x^2=0,92 | | 18x(200+9)=(18x200)+(18x9) | | 4x+3x^2=0,92 | | f‐6=‐2f+3(f‐2) | | (13x-95)=180 | | 21x+14-(11x-16)+5x=0 | | 3z+9+14z=4z+53z+9+14z=4z+53 | | 4(-2k-8)=6(k-18) | | 23y+50+27y=50y+5023y+50+27y=50y+5023 | | 15x=(x-3) |

Equations solver categories